CEA as a prognostic index in colorectal cancer - Forones, Nora Manoukian (1997)
INTRODUCTION: The carcinoembryonic antigen, CEA, is the tumor marker most used in colorectal patients, principally during follow up after radical surgery. High serum CEA level before surgery is often associated with worse prognosis, in some studies. OBJECTIVE: The purpose of this study was to evaluate the preoperative carcinoembryonic antigen levels (CEA) and the frequency of recurrence. MATERIAL AND METHODS: Eighty-three patients with colorectal cancer at Dukes stages A, B or C were evaluated retrospectively. The patients' follow up was at least two years or to death. CEA was detemined in serum by enzyme immunoassay (Sorin Biomedica), normal value 0-5ng/mI. RESULTS: Disease recurrence was observed in 32 patients (38.5%), 13 Dukes B and 19 Dukes C. Seventy five per cent of the patients with CEA higher than 10ng/ml relapsed and 80% of the patients without recurrence had normal CEA. Disease recurrence in patients with preoperative elevated CEA occurred during the first year of follow up in 56% of the patients. CONCLUSION: Although the tumor stage is today the most valuable prognostic variable in colorectal cancer, the preoperative CEA value can provide some additional information in the prognosis of the patient.